Following a strategy, I found the error in the achievement of intermediate second-grade students in Arabic grammar - شبرم غضيب الحمداوي بهاء (Journal of College of Education, 2021)
This research aims to identify the effect of a strategy that created the error in the achievement of the second intermediate grade students in the subject of Arabic grammar. The study was conducted in the Shahid Abdul Saheb Dakhil Boys Intermediate School, the research sample consisted of (76) students of the second intermediate grade in middle and high schools in Al-Amara City Center, the experiment was conducted during the first semester of the academic year (2018-2019), and the researcher used the experimental design with partial control, and the researcher formulated behavioral goals with 48 goals, and the instructional plans for the experimental group and the control group with (10) plans for the experimental group and the group The control group, and the researcher built a research tool that was represented by an achievement test, and the results of the research reached the superiority of the experimental group students over the control group in the test of avoiding spelling errors.